Complex Networks & Their Applications X Volume 2, Proceedings of the Tenth International Conference on Complex Networks and Their Applications COMPLEX NETWORKS 2021 - Benito, Rosa Maria; Cherifi, Chantal; Cherifi, Hocine; Moro, Esteban; Rocha, Luis M.; Sales-Pardo, Marta; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book highlights cutting-edge research in the field of network science, offering scientists, researchers, students, and practitioners a unique update on the latest advances in theory and a multitude of applications. It presents the peer-reviewed proceedings of the X International Conference on Complex Networks and their Applications (COMPLEX NETWORKS 2021). The carefully selected papers cover a wide range of theoretical topics such as network models and measures; community structure, network dynamics; diffusion, epidemics and spreading processes; resilience and control as well as all the main network applications, including social and political networks; networks in finance and economics; biological and neuroscience networks, and technological networks.
Keywords: Dynamics; Nonlinear theories; Computational intelligence; Graph theory; Applied Dynamical Systems; Computational Intelligence; Graph Theory; Computer networks -- Congresses; System analysis -- Congresses; Systems engineering -- Congresses